1986
DOI: 10.1111/j.1469-7998.1986.tb03613.x
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive output of frogs Rana temporaria (L.) with particular reference to body size and age

Abstract: Measurements were made on 274 spawn clumps and 271 adult frogs in three consecutive years at breeding sites in the west of Ireland. Mean clutch size was 1008 ± 20 ova, mean egg diameter was 2·32 ± 0·01 mm, and mean clutch weight was 11·62 ± 0·37 g. At any particular body length, larger clutch sizes were associated with smaller egg sizes and vice versa. Clutch size, egg size and clutch weight all increased allometrically with body size. The bigger females produced more and smaller eggs and a heavier clutch, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 17 publications
5
54
1
Order By: Relevance
“…The positive association between body size and egg size is commonly observed among anurans (review in Kusano and Hayashi, 2002), whereas the relationship between age and egg size shows a less consistent pattern. In some species, egg size increases with age (Gibbons and McCarthy, 1986;Berven, 1988), whereas in others, no relationships are observed after controlling for body size variation (Tejedo, 1992;Kusano and Hayashi, 2002; the present study).…”
Section: Body Size Age and Reproductive Investmentmentioning
confidence: 54%
See 1 more Smart Citation
“…The positive association between body size and egg size is commonly observed among anurans (review in Kusano and Hayashi, 2002), whereas the relationship between age and egg size shows a less consistent pattern. In some species, egg size increases with age (Gibbons and McCarthy, 1986;Berven, 1988), whereas in others, no relationships are observed after controlling for body size variation (Tejedo, 1992;Kusano and Hayashi, 2002; the present study).…”
Section: Body Size Age and Reproductive Investmentmentioning
confidence: 54%
“…In these species, size-dependent differences in fecundity may thus arise from differences in age at maturity, that is, from different tradeoffs between the expected number of reproductive episodes and the reproductive success of each episode (Shine, 1988). Furthermore, age may directly affect variation in fecundity if the proportion of resources allocated to reproduction, rather than to growth and self-maintenance, increases with age (Gibbons and McCarthy, 1986;Berven, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable variation in the number of fertilized eggs per clutch has been reported previously for R. temporaria (5-100%) 22,23 . By experimentally rearing 25 pirated and 31 non-pirated clutches we found that under specific circumstances clutch piracy helps to increase the number of eggs fertilized per clutch (Fig.…”
mentioning
confidence: 61%
“…In species where most individuals breed only once, such as Rana dalmatina (Guarino et al, 1995), other criteria than previous experience may prevail in migration guidance. On the other hand, despite an indeterminate growth, a positive relationship between age and body size has never been evidenced in frogs of the genus Rana (Gibbons & McCarthy, 1986 ;Augert, 1992). As a consequence, a larger body size does not suggest a previous experience of breeding migration.…”
Section: Discussionmentioning
confidence: 99%